Gestão da educação corporativa para a aprendizagem e desenvolvimento organizacional e pessoal : percepção dos funcionários de banco público - Gonçalves, Carlos Eduardo Cavalcanti (2024)
Financial institutions have the constant challenge of providing their employees, at all levels, with sufficient educational improvement to meet the demands of the current reality, and this can be done through what is known as corporate education. In order to contribute to the subject, this dissertation is the result of research at a Brazilian public bank. The general objective was to analyse the perceptions of employees at branches of a public bank regarding the corporate education offered to them for organisational and professional learning and development, and to propose adjustments aimed at improving it. In terms of methodology, the sample was made up of employees from six branches of the bank, located in João Pessoa/PB. This research was carried out by applying a questionnaire to the employees, making it a qualitative, quantitative and descriptive study. All the employees who agreed to take part answered the questionnaire. The main results revealed a predominantly positive perception of the aspects assessed, despite significant levels of disagreement and dissatisfaction, often above 20 per cent, even on the most positively perceived issues. This highlights the need to implement a more effective feedback system to capture and respond to employee concerns in a timely manner. One of the indications that was evident in the results is that employees want face-to-face or semi-presential training to be expanded and/or resumed, refuting many of those who are 100 per cent e-learning. They believe that face-to-face training promotes greater interaction and practical application of content, and increases the flexibility of educational programmes to meet employees' individual preferences in terms of learning format and modality. Another desire is for more practical courses, applied to the operational reality of day-to-day work. As a proposal, we suggest courses and activities that could be implemented to meet these demands in order to increase satisfaction with the activities of the corporate university. The main conclusions are that the virtual world cannot bring the same interaction and satisfaction as face-toface meetings, but that neither should be discarded and that the best way is to offer a hybrid catalogue that mixes face-to-face and virtual courses.